Gender accelerators: Women and men leading the way on local forest tenure reform: Training handbook - Jhaveri, Nayna J.; Monterroso, Iliana; Larson, Anne M. (Center for International Forestry Research, 2021)
This training handbook accompanies the publication, Forest tenure pathways to gender equality: A practitioner’s guide. The approximately six-hour course describes an approach to building up a core group of women and men leaders who will champion the forest tenure pathway to gender equality. Using this approach requires a good understanding of the conditions under which diverse leadership can flourish and capably create change. This work is aligned with step three of the three-step change pathway for gender equality in the Practitioner’s guide: Realize. The content of the handbook and its handouts are illustrative and can be tailored to different training requirements. For example, if the course is used for government staff or members of a non-governmental organization, the content and exercises can be adjusted to suit the knowledge background and interests of participants.